(untitled) (Stato, Chiese e pluralismo confessionale, 2013)
contributo sottoposto a valutazione SOMMARIO: 1. L’autonomia ex art. 33 della Costituzione quale carattere necessario dell’istituzione museale – 2. L’utilità sociale dei musei ecclesiastici – 3. Le fonti canonistiche – 4. L’introduzione della sussidiarietà orizzontale come traguardo culturale – 5. Volontariato culturale e micro-sussidiarietà: Abstract. The admission of ecclesiastic museums in cultural heritage: some reflection in constitutional law perspective Since museum reached its public function, as the people museum, management problems have emerged for the difficult compatibility between works of art and mass visits, for the lack of resources, for the relative difficulties of conservation and preservation, for the typical characteristics of museums, that are structured as private building and not to be opened to a various public. So we have to outline appropriate and productive management forms, to state coordinating techniques with other cultural or not cultural institution, to solve interpretation problems that stress the current management. On the other hand it is important to improve the quality of personnel and to increase the appropriate service structures to make an analysis of users needs and to simplify, with marketing and communication methods and instruments too, the access of collectivity to museums. With these perspectives, individual contribution and the help of little voluntary associations, which are promoted and supported, can give in the field of museums a micro-subsidiarity perspective, that can be even tested.